The Impact of Remittances on Socio-Economic Development - The Case of Kosova - Cuci, Qëndresë (European Journal of Economics and Business Studies, 2016)
Another important indicator of a country’s economic development is the inflation and the unemployment rate, and according to the latest report of Kosova Agency of Statistics, the percentage of unemployment in Kosova is around 30.9 percent and this is an indicator that the unemployment rate has been reduced compared to the previous years, on the other hand, the number of families receiving remittances is decreased for 2.6 percent compared to 2011 according to a ASK report.1 Also the number of startups in 2012 has increased to 7,8792 which created new jobs. So, remittances re very important especially for developing countries such as Kosova. Taking into consideration the fact that Kosova is in the development phase, and the standard of living is very low, the number of population seeking to migrate is increasing continuously. According to statistics, the number of male migrants is higher compared with female igrants and rural settlements have shown an increase in migration compared to urban settlements. Our community is convinced that diaspora is an indicator in the economic development of our country, such as skills development for knowledge that they would benefit from, education, for consumption and commercial investments, all these for a higher standard of living.
Keywords: remittances, migration, income growth, efficiency, sustainable development, economic growth, social welfare.